Clinical Influenza Testing Practices in Hospitalized Children at United States Medical Centers, 2015-2018. Issue 1 (13th October 2021) - Tenforde, Mark W; Campbell, Angela P; Michaels, Marian G; Harrison, Christopher J; Klein, Eileen J; Englund, Janet A; Selvarangan, Rangaraj; Halasa, Natasha B; Stewart, Laura S; Weinberg, Geoffrey A; Williams, John V; Szilagyi, Peter G; et al.
Abstract: At nine US hospitals that enrolled children hospitalized with acute respiratory illness (ARI) during 2015-2016 through 2017-2018 influenza seasons, 50% of children with ARI received clinician-initiated testing for influenza and 35% of cases went undiagnosed due to lack of clinician-initiated testing. Marked heterogeneity in testing practice was observed across sites.